54.1k views
3 votes
Suppose the function of h is defined, for all real numbers as follows: (f) x = -3 if x is <) 3 if x is =0 -2 if x is > 0

User Jogy
by
4.8k points

1 Answer

4 votes

Answer:

See explanation

Explanation:

The question is not properly presented; I will answer this with the following similar question.


h(x) = -(1)/(3)x^2 + 4 ---
x \\e 2


h(x) = -4 ---
x= 2

Required


h(-5)\ \&amp;\ h(2)

Calculating h(-5)

This implies that: x = -5


-5 \\e 2

So, we make use of:


h(x) = -(1)/(3)x^2 + 4

Substitute -5 for x


h(-5) = -(1)/(3) * (-5)^2 + 4


h(-5) = -(1)/(3) * 25 + 4


h(-5) = -(25)/(3) + 4

Take LCM


h(-5) = (-25+12)/(3)


h(-5) = -(13)/(3)

Calculating h(2)

This implies that: x = 2


2 = 2

So, we make use of:


h(x) = -4

Substitute 2 for x


h(2) = -4

Use the above explanation to answer your question

User Duffydake
by
4.9k points